Developing gallium nitride-based inverters for high-performance photovoltaic integration in alternating current grids - Soomar, Arsalan Muhammad; Musznicki, Piotr (International Journal of Electrical and Computer Engineering (IJECE), 2025)
This study introduces a gallium nitride (GaN) based inverter optimized for alternating current (AC) grid integration, featuring a novel phase-locked loop (PLL) controller enhanced with sliding mode control (SMC). This hybrid PLL-SMC approach significantly improves power delivery from photovoltaic (PV) sources, achieving a total harmonic distortion (THD) of 5% and a maximum power point tracking (MPPT) efficiency of 99.1%. Extensive testing demonstrates the inverter's superior performance in grid synchronization, efficiency, and power quality compared to conventional inverters. The results underscore the critical role of advanced GaN-based inverters in enhancing solar energy utilization and advancing renewable energy integration into AC grids. This work sets a new benchmark for PV system integration, contributing to the broader adoption of renewable energy technologies.